PENGARUH METODE EVERYONE IS TEACHER HERE TERHADAP AKTIVITAS DAN HASIL BELAJAR GEOGRAFI - Indah Nurlaila Lestari; Sumadi Sumadi; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2015)
This research was aimed at finding out (1) the difference between the students activites, (2) students pre-test result, (3) the students achievement by using learning method of everyone is teacher here and conventional method,(4) the effect of learning method of everyone is teacher here on the students achievement. Quasi experiment was used in this research. The populations in this research were 299 students with research samples of 78 students. To analyze the data, T-Test and linear regression analysis were used. The results showed that (1) there was a difference between the students activites during learning process by using method of everyone is teacher here and conventional method, (2) there was no difference between students pre-test result experiment class and control class, (3) there was a difference between the students achievement by using everyone is teacher here method and conventional method, (4) there was an effect of learning method of everyone is teacher here on the students learning achievement of geography.Penelitian ini bertujuan untuk mengetahui (1) perbedaan aktivitas belajar siswa, (2) nilai Pre-test siswa, (3) hasil belajar menggunakan metode Everyone Is Teacher Here dan metode konvensional, (4) pengaruh metode Everyone Is Teacher Here terhadap hasil belajar. Penelitian menggunakan metode eksperimen kuasi. Populasi dalam penelitian ini sejumlah 299 siswa dengan sampel penelitian sebesar 78 siswa. Teknik analisis data yang digunakan adalah uji t dan analisis regresi sederhana. Hasil penelitian menunjukkan bahwa (1) Ada perbedaan dalam aktivitas belajar siswa menggunakan metode Everyone Is Teacher Here dan metode konvensional, (2) Tidak terdapat perbedaan nilai Pre-test siswa kelas eksperimen dan siswa kelas kontrol, (3) Terdapat perbedaan hasil belajar siswa menggunakan metode Everyone Is Teacher Here dan metode konvensional, (4) Terdapat pengaruh metode Everyone Is Teacher Here terhadap aktivitas dan hasil belajar Geografi siswa.Kata kunci: metode pembelajaran everyone is teacher here, aktivitas, hasil belajar.